The American Newsroom : A History, 1920-1960 - Mari, Will (William) (Book collections on Project MUSE., 2021)
"The story of the American newsroom is that of modern American journalism. This holistic history tells that story, from the 1920s through the 1960s, in a time of great change and controversy in the field, when journalism was produced in "news factories" by news workers with dozens of different roles, and not just once a day, but hourly, using the latest technology and setting the stage for the later century's information economy"--